HUBUNGAN TRANSPARANSI DAN AKUNTABILITAS DENGAN PARTISIPASI KOMUNITAS SMA NEGERI 26 BONE - Susisanti Susisanti (Manajemen Pendidikan, 2022)
This article aims to analyze and test the relationship between transparency, accountability, and community participation. This study was conducted at SMA Negeri 26 Bone using a quantitative approach through a correlational study. Respondents in this study found 87 people, consisting of 28 teachers who were taken as a whole, 53 parents of students, and 6 school committee members. The data collection technique used is to distribute research respondent questionnaires. The data obtained through the questionnaire were then analyzed using product moment correlation analysis and multiple correlations. The results of this study have proven that: 1) there is a positive and significant relationship between transparency and community participation; and 2) there is a positive and significant relationship between accountability and community participation. Thus, the application of transparency in education management will encourage public awareness to participate in helping to improve the quality of education in schools.